Effect of locally formulated recovery drink on perfomance and muscle soreness in adolescent soccer players - Mardatillah, Mutiah; Setiawan, Budi; Marliyati, Sri Anna (UIR Press, 2025)
Background: Adequate post-exercise nutrition is critical for recovery and performance, especially among adolescent athletes undergoing growth and development. However, research on locally formulated and culturally relevant recovery drinks for Indonesian youth remains scarce. This study addresses that gap by testing a novel recovery drink using familiar local ingredients. Research Objectives: This study aimed to analyze the effects of consuming a healthy recovery drink made from low-fat milk, banana, cocoa powder, and gulo puan on muscular strength, muscular endurance, VO2 max, and muscle soreness in adolescent soccer athletes. Methods: A randomized pretest-posttest control group design was conducted with 16 adolescent soccer players (aged 15-18) from Sriwijaya State Sport School, Palembang, over a 5-day intervention. Performance indicators included handgrip strength (dynamometer), vertical jump, muscular endurance (Muscular Fitness Test), VO2 max (multistage fitness test), and muscle soreness (visual analog scale). Finding/Results: The results showed that the consumption of the healthy recovery drink significantly improved handgrip strength, vertical jump performance, and muscular endurance in the intervention group. The reduction in upper body muscle soreness post-exercise was also greater in the intervention group compared to the control group. Conclusion: The recovery drink formulated in this study has the potential to serve as an effective nutritional alternative for adolescent football athletes in the post-training recovery phase to enhance athletic performance by promoting energy replenishment and muscle regeneration. The short duration of the study and limited sample size may have restricted the ability to detect long-term effects, particularly on aerobic performance. Future research with larger samples and extended intervention period is recommended.